Physical properties and surface morphology of natural rubber latex films intended for seedling bag application (Journal of Rubber Research, 2012)
Natural rubber (NR) latex concentrate of the Hevea brasiliensis species is used to fabricate a seedling bag using a typical latex dipping process. The latex film from the bag demonstrated excellent physical properties such as strength and stiffness, to form the intended product. Incorporating non rubber materials such calcium carbonate, corn starch or fertilizer into the bag, increased the stiffness of the latex film with the reduction in its strength properties. Under natural environmental conditions, the physical properties of the film started to show reduction after two months buried in soil. Substantial reduction in weight of the film was due to NR latex biodegradation expected to occur readily during the soil burial. The degradation of the film surface was obtained from FESEM micrographs as cracks and cavities at the degraded area. The added non rubber material as filler, namely corn starch and fertilizer, further amplified the biodegradation rate of the film, while ground calcium carbonate slowed down the biodegradation process of the film. The study confirmed NR latex is a suitable alternative choiceto synthetic materials as seedling bag base material. The NR latex seedling bag is in fact an environmentally friendly seedling bag which is able to retain the physical performance while in use and able to self-decompose under soil burial.
Keywords: Agricultural waste management; Environmental exposure; Non rubber filler; NR latex